Use of healthcare administrative claims data in observational studies of antirheumatic drug effects on pregnancy outcomes: A scoping review - Shenthuraan Tharmarajah; Araniy Santhireswaran; Yasmeen Ameeriar; Lisa M. McCarthy; Dharini Mahendira; Howard Berger; Mina Tadrous; Sara J. T. Guilcher (PLoS ONE, 2025)
The safety of antirheumatic drugs in pregnancy and their impact on maternal and neonatal outcomes are understudied. Despite pregnant individuals being excluded from clinical trials, their continued use of medications raises the importance of addressing knowledge gaps regarding safety and impact on outcomes. A scoping review was conducted following JBI methodology and PRISMA reporting guidelines to describe how antirheumatic drugs and associated adverse pregnancy outcomes have been investigated in observational studies using claims data. Electronic databases (MEDLINE (Ovid), Embase (Ovid), and CINAHL (EBSCO)) and grey literature were searched for observational studies using claims data to evaluate antirheumatic drug effects on pregnancy outcomes in individuals with rheumatic diseases. Of 4,325 articles identified, 38 eligible articles were included. The effects of conventional synthetic disease-modifying antirheumatic drugs (n =  37, 97.4%) and tumor necrosis factor inhibitor biological agents (n =  23, 60.5%) were extensively reported. Preterm birth (n =  25, 65.8%), preeclampsia (n =  17, 44.7%), stillbirth (n =  17, 44.7%), caesarean delivery (n =  16, 42.1%), and congenital anomalies (n =  14, 36.8%) were the most reported adverse pregnancy outcomes. Of 14 studies reporting congenital anomalies, 12 (85.7%) specified ICD codes and 4 (28.6%) specified validated definitions for identification in claims data, the most of any reported adverse pregnancy outcome. We found considerable ambiguity and heterogeneity in adverse pregnancy outcome definitions in claims data. There is a need for greater transparency and consistency in outcome reporting in observational studies using claims data. Protocol registration details: OSF, https://osf.io/5e6tp